Transformasi Spiritual dalam Haul Wali: Perspektif Fenomenologi Alfred Schutz Pada Jemaah Abah Guru Sekumpul - Pratama, Muhammad Yogy Qorri Dwi; Mahzumi, Fikri (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2024)
The tradition of Haul KH. Muhammad Zaini Bin Abdul Ghani (Abah Guru Sekumpul) in Martapura, south Kalimantan is a phenomenon of contemporary religiousness in Indonesia. This haul tradition has attracted the attention of muslims from various religious, cities dan countries. Abah Guru Sekumpul is a charismatic figure that some muslims believe as a guardian, so that after his death, thousands of muslims attended his haul. This article aims to discover the aspects of spiritual transformation in the congregation by focusing o the personal motives of congregations using the phenomenological theory of Alfred Schutz. This research method uses qualitative research methods. The case study approach became the basis of this study by using data from observations and interviews on key sources of a number of six people. The results of this study show that there are aspects that influence the spiritual transformation of the congregation based on personal motives. There are aspects that affect the spirituality of the congregation both subjectively and objectively. The haul tradition has spiritual motives and financial motives.